Contribuições para a pirólise da casca de cacau em leito de jorro : estudos da fluidodinâmica experimental e simulação via CFD - Almeida, Priscilla de Souza (2016)
The replacement of non-renewable resources for renewable resources is a major desired objective worldwide. Brazil is a country that has been successful in this race for an energy matrix where alternative sources are prevalent. Biomass is a promising renewable source that if used with appropriate technology is able to generate products with high energy potential. Pyrolysis stands out in the scene of thermochemical conversion technologies, being the most suitable reactors in the process those able to provide an excellent mix of components to be pyrolyzed. The spouted bed, to be equipment which provides a high contact between solids and fluid, fits well as a pyrolysis reactor. Therefore, a fluid dynamic study of the behavior of the particles involved in this process is one of the basic steps for applying this technique. The cocoa shell residue is the main residue of cocoa process, comprising about 80% of the fruit. Normally used for animal feed production and fertilizer, this biomass can be viewed as a convenient energy source. This work has as main objective to study the fluid dynamics of a binary mixture consisting of cocoa shell particles and sand in a spouted bed. The minimum spouting velocity and stable pressure drop were evaluated through statistical analyzes for different static bed heights (6, 8 and 10 cm) and mass fractions of cocoa shell (25, 50 and 75%). The segregation of the mixtures was analyzed in the bed heights and mass fractions of cocoa shell adopted in fluid dynamic study, varying the velocity of the air at 10, 20 and 30% above the minimum spouting velocity. The stable spouted regime was established in the studied experimental region. It was found that the minimum spouting velocity was not influenced by variations in mass fraction, unlike the stable pressure drop which suffered interference as much as the mass fraction and the static bed height. The segregation of particles was observed in the regions of the top and bottom of the bed. CFD simulations were performed using the Eulerian model to describe the gas-solid flow in spouted bed and using a two-dimensional structured mesh. Simulations have shown agreement with the experimentally observed relative to the fluid-dynamic behavior and segregation in the bottom of the bed.